Differential microstrip antenna array design - Liang Yusheng (Nanyang Technological University, 2024)
To investigate how to optimize the performance of single-ended patch antennas with different feed- ing methods, this study conducted simulations to compare the advantages and disadvantages of microstrip line feeding and coaxial probe feeding, exploring their suitability for narrowband and wideband applica- tions. Additionally, in order to explore the application of Balun technology in differential-fed antennas, the study optimized the antenna structure to enhance impedance matching, directivity, and phase control accuracy. Particularly in array antenna feed networks, the application of Balun was further examined. Through careful design, the study reduced signal loss in the feed network, improved the overall efficiency of the array antenna, and maintained good impedance matching and radiation performance. This research also conducted far-field electromagnetic analysis of the antennas and used HFSS simulation methods to design a single-ended microstrip antenna, a dual-band circular antenna, and a dif- ferential microstrip antenna with an optimized Balun feed network. The simulation results show that these designs exhibit excellent performance in their respective application scenarios, demonstrating great potential for further optimization and application in modern wireless communication systems.